Sam Rayburn Leading the Lawmakers - Allen, Edward (Ency. Britannica Press Chicago, IL, 1963)
In the 1890's as a youth, Sam Rayburn heard his Congressman speak in Bonham, Texas, and vowed to become a Congressman.
Keywords: Rayburn, Sam -- 1882-1961 -- Juvenile literature; United States -- Biography -- Juvenile literature; Texas -- Politics and government -- Juvenile literature. -- 1865-1950